2009
DOI: 10.1001/archophthalmol.2009.218
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Metastasis of Cutaneous Melanoma to Conjunctival Lymphatics

Abstract: RESEARCH LETTERS Retrograde Metastasis of Cutaneous Melanoma to Conjunctival Lymphatics C onjunctival metastasis from cutaneous melanoma typically reaches the conjunctiva by hematogenous routes. 1-7 We report a unique case of presumed retrograde conjunctival metastasis via lymphatic channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Rarely, abnormal conjunctival pigmentation mimicking primary CM can occur in patients with a prior diagnosis of cutaneous melanoma. Reports documenting conjunctival metastasis have included patients with cutaneous melanoma arising at both distant (trunk [22, 23], axilla [24], scapula [25], vaginal mucosa [26]) and local (pre-auricular [27], temple [28], neck [29]) sites. Conversely, there have been rare reports of primary CM metastasizing to the eyebrow and cheek [30]; however, it is unclear whether or not the histopathological findings in these patients were consistent with in-transit metastasis or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely, abnormal conjunctival pigmentation mimicking primary CM can occur in patients with a prior diagnosis of cutaneous melanoma. Reports documenting conjunctival metastasis have included patients with cutaneous melanoma arising at both distant (trunk [22, 23], axilla [24], scapula [25], vaginal mucosa [26]) and local (pre-auricular [27], temple [28], neck [29]) sites. Conversely, there have been rare reports of primary CM metastasizing to the eyebrow and cheek [30]; however, it is unclear whether or not the histopathological findings in these patients were consistent with in-transit metastasis or not.…”
Section: Discussionmentioning
confidence: 99%
“…In-transit metastasis occurs in up to 4% of cases of cutaneous melanoma and is a phenomenon attributed to intralymphatic spread resulting in a second lesion >2 cm from the primary tumour but not beyond the regional nodal basin [31]. While conjunctival metastasis from cutaneous melanoma typically occurs via haematogenous routes, Shields et al [27] reported a very peculiar case of retrograde conjunctival metastasis via lymphatic channels of a cutaneous melanoma arising in the pre-auricular skin.…”
Section: Discussionmentioning
confidence: 99%
“…An overview of 19 conjunctival metastases of cutaneous melanomas showed a poor survival, ranging from <1 to 16 months [11]. However, it has to be noted that survival data in 5 out of 19 reported cases were absent [2,10,12,13,14,15,16,17,18,19,20]. …”
Section: Discussionmentioning
confidence: 99%